SELEBRITY OF STUDENT ROLE IN CAMPUS - Zuhroh, Ni’matuz; Wisadirana, Darsono; Kanto, Sanggar; Umanailo, M Chairul Basrun; Mardiyono, Mardiyono (Advances in Social Sciences Research Journal, 2020)
Celebrity students, namely students whose duties besides studying at tertiary institutions also work as celebrities, among others as models, singers, endorsements, celebrities, etc. This study aims to find out how the role of celebrity students in Malang Brawijaya University, the causes and impacts. This study uses a qualitative phenomenological approach that is described descriptively with data sources consisting of University of Brawijaya University Malang celebrities. Data collection techniques in this study are observation, interviews, and documentation. The subject selection technique used was purposive sampling and snowball technique. The research subjects were 10 celebrity students from various faculties at Brawijaya University Malang. The validity of the data in this study uses source triangulation techniques, and data analysis uses Milles and Hubberman's interactive analysis. The results of this study indicate that the students of Celebrity Brawijaya University Malang. Students are not only expected to be able to contribute their knowledge to the community in the surrounding environment but also in the campus environment as an example of the students described above. From various student labels, in this study, students contribute to campus activities at. Celebrity students in this study play a role with Miss Universe Universitas Brawijaya, MC at campus events such as Graduation events, Dies Natalis etc., there are also those who come to the invitation on behalf of students outside the institution, there are also those who love, dance at every performance held on campus .